Surface plasmon polaritons with plasma frequencies above 1 eV in Sn‐doped In2 O3. Issue 2 (20th October 2015) - Kalusniak, Sascha; Orphal, Laura; Schäfer, Peter; Sadofev, Sergey
Abstract: Sn‐doped In2 O3 films with free‐electron concentration varied up to 1.7 × 10 21 cm − 3 are prepared by molecular beam epitaxy. In this way, a metallic Drude‐type dielectric function with a negative real part extending beyond λ c = 1050 nm is created. Despite essentially polycrystalline structure of the layers, the plasmonic damping Γ is found not to exceed 70 meV in the entire doping range making excitation of low‐loss surface plasmon polaritons at frequencies fully covering the telecommunication band feasible. A monotonically increasing discrepancy between the carrier concentration obtained from Hall‐effect and the concentration extracted from fitting the optical spectra hints at a change of the band‐structure related parameters of In2 O3 with increasing Sn‐doping.